2020
DOI: 10.1155/2020/5867617
|View full text |Cite
|
Sign up to set email alerts
|

Left Atrial Strain as Evaluated by Two-Dimensional Speckle Tracking Predicts Left Atrial Appendage Dysfunction in Chinese Patients with Atrial Fibrillation

Abstract: Left atrial appendage (LAA) dysfunction identified by transesophageal echocardiography (TEE) is a powerful predictor of stroke in patients with atrial fibrillation (AF). The aim of our study is to assess if there is a correlation between the left atrial (LA) functional parameter and LAA dysfunction in the AF patients. This cross-sectional study included a total of 249 Chinese AF patients who did not have cardiac valvular diseases and were undergoing cardiac ablation. TEE was performed in all the patients who w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
1
3
0
1
Order By: Relevance
“…We found that the LVEF significantly decreased while LAV (LAVI) substantially increased in the thrombus group compared to the non-thrombus group (P = 0.001). This agrees with the research conducted by Wang et al [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…We found that the LVEF significantly decreased while LAV (LAVI) substantially increased in the thrombus group compared to the non-thrombus group (P = 0.001). This agrees with the research conducted by Wang et al [ 16 ].…”
Section: Discussionsupporting
confidence: 94%
“…Kuppahally et al revealed an inverse association of fibrosis degree assessed by LGE CMR and LA strain, notably in cases of persistent AF in comparison with acute forms 39 . Recent prospective long‐term follow‐up studies demonstrated that longitudinal strain is a potent and independent predictive factor of future AF occurrence in different cohorts 40,41 . Longitudinal strain predicts prognosis in AF, independently of cardiovascular risk factors.…”
Section: Clinical Evaluation For Assessing Atrial Fibrosis and Afmentioning
confidence: 99%
“…39 Recent prospective longterm follow-up studies demonstrated that longitudinal strain is a potent and independent predictive factor of future AF occurrence in different cohorts. 40,41 Longitudinal strain predicts prognosis in AF, independently of cardiovascular risk factors.…”
Section: Speckle Tracking Echocardiography (Ste)mentioning
confidence: 99%
“…Not at all like the ongoing investigation by Wang et al [35], they didn't see the CHA2DS2-VASc score as altogether connected with LAA brokenness, and this score was not a perfect stage to foresee dangers related with stroke utilizing the LAT esteem as a comparator. This irregularity was additionally seen in past investigations [36,37].It is clear that the scoring system includes an assessment of the risks of early stroke, including those that cause vascular wall injury and hypercoagulable status [38].…”
Section: )mentioning
confidence: 91%